Large scale synthesis of graphene quantum dots (GQDs) from waste biomass and their use as an efficient and selective photoluminescence on-off-on probe for Ag+ ions - Suryawanshi, Anil; Biswal, Mandakini; Mhamane, Dattakumar; Gokhale, Rohan; Patil, Shankar; Guin, Debanjan; Ogale, Satishchandra (Nanoscale, 2014)
Graphene quantum dots (GQDs) are synthesized from bio-waste and are further modified to produce amine-terminated GQDs (Am-GQDs) which have higher dispersibility and photoluminescence intensity than those of GQDs. A strong fluorescence quenching of Am-GQDs (switch-off) is observed for a number of metal ions, but only for the Ag+ ions is the original fluorescence regenerated (switch-on) upon addition of L-cysteine.

Low temperature grown CuBi2O4 with flower morphology and its composite with CuO nanosheets for photoelectrochemical water splitting - Patil, Rupali; Kelkar, Sarika; Naphadeab, Rounak; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
In this work we highlight a peculiar synthesis protocol for the p-type ternary metal oxide system of copper bismuth oxide (CuBi2O4), which yields a highly crystalline spherulitic morphology at a low temperature of 78 degrees C. We associate this growth with the hydrogen bonding effects imparted by the ethanol-water co-solvent system used for the synthesis. We present a detailed growth mechanism by evaluating different synthesis conditions systematically. Furthermore we show that upon the use of the non-stoichiometric (excess copper) precursor mixture under the same experimental conditions the growth of spherulitic CuBi2O4 changes the size and type of the spherulites. Interestingly, careful optimization of the nonstoichiometric synthesis presents a complete impediment to the spherulitic growth and produces a composite of nanorods of CuBi2O4 and nanosheets of CuO. This anisotropic nanocomposite shows an order of magnitude higher surface area as compared to spherulitic CuBi2O4. Since both CuBi2O4 and CuO are visible light absorbing p-type semiconductors, when the synthesized nanocomposite materials are examined as photoelectrochemical (PEC) photocathodes for water splitting, they show a remarkable dependence on the morphology and phase constitution. Almost 13-fold stronger PEC response is observed as the morphology changes from spherulites to nanorods.

Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells